Exploring the dating of “dirty” speleothems and cave sinters using radiocarbon dating of preserved organic matter - Blyth, Alison; Hua, Q.; Smith, A.; Frisia, S.; Borsato, A.; Hellstrom, J. (Elsevier, 2017)
Speleothems and other carbonate deposits such as tufa containing high proportions of detrital material can be difficult to chemically date due to detrital thorium levels causing a high level of error in conventional U-Th disequilibrium dating. Here we investigate the use of an alternative technique centring on radiocarbon dating of organic matter preserved within the detrital fraction. Non-acid soluble humic, particulate and detritally absorbed organic matter was recovered from eight samples from a flowstone sinter formed within a roman aqueduct at Trento in Italy with a maximum age of 100 CE (1850 cal yr BP), and two repeat samples from a dripstone formed within the 20th Century on a wire fence at Lilly-Pilly Cave, Buchan Caves Reserve in Victoria, Australia. In the aqueduct samples the median calibrated 14C ages ranged from 2232 to 2889 cal yr BP, with 95.4% probability age range in the youngest and oldest samples of 2153–2337 and 2342–3449 cal yr BP respectively. The median age of the more modern dripstone was 336 cal yr BP, with a 95.4% probability age range of 148–486 cal yr BP. These results provide very approximate ball-park estimates of the age of the sample, but are consistently too old when compared to the known maximum ages of formation. It is hypothesised that this offset is due to a combination of the nature of the organic carbon transported from the source organic matter pools, and reworking of both modern and old organic carbon by in situ microbial communities.